A dual-confined lithium nucleation and growth design enables dendrite-free lithium metal batteries. Issue 21 (13th May 2022) - Li, Lun; Fu, Huaqiang; Yang, Jinlong; Wang, Pengyan; Zhang, Huazhang; Zhao, Xin; Xiao, Zhitong; Liu, Zhenhui; Kou, Zongkui; Wang, Zhenbo; He, Daping
Abstract : A dual-confined Li nucleation and growth design is enabled by the synergistic effect of doped N sites and Ag NCs, which produces uniform Li nucleation. The induced Li–Ag alloy promotes epitaxial growth of Li until a smooth/dense surface is formed. Abstract : Suppressing lithium (Li) dendrite growth is expected to enable the construction of a reliable Li metal anode for high energy density batteries. However, it is still a huge challenge to synchronize uniform nucleation and controllable growth for complete suppression of Li dendrite formation, because independent confinement of nucleation or growth is hampering the rational design of current Li anodes. Herein, we demonstrate that by anchoring silver (Ag) nanocrystals on the superlithiophilic nitrogen (N) doping site in reduced graphene oxide (Ag/N-rGO) supports, a dual-confined Li nucleation and growth is synchronously realised for producing a stable Li metal anode. Our dual-confined design gives abundant Ag/N interface sites which direct the uniformity of Li nucleation, and provides evenly sized Ag nanocrystals adjacent to N sites which further impose a complete restriction on the disordered Li growth, as rationalized by a combined study comprising experimental observation and theoretical simulations. As a result, our dual-confined Li anode shows a dendrite-free microstructure even after high-capacity and repeated Li plating/stripping. It shows highly stable coulombic efficiency over 99.1% and ultra-long cycle life over 1200 h upon cycling at 2 mA cm −2 . An LFP//Li@Ag/N-rGO full cell manifests a superior rate capability and a high cycling stability (110.8 mA h g −1 at 1C) over 500 cycles.